Migración y minería en el corregimiento de Carangas (actual Bolivia), siglo XVII - Gil Montero, Raquel (Jahrbuch für Geschichte Lateinamerikas, 2018)
During colonial times, Carangas was one of the most depopulated provinces of Charcas (present-day Bolivia), partly because of its obligation to send tributaries to work in the mines and mills of Potosí. This demographic trend was subtly reversed towards the middle of the seventeenth century, when silver veins were discovered in Carangas. Those mines required laborers, although in a relatively small number. The main purpose of this article is to analyze this double process: on the one hand, the emigration of manpower to different mining and agrarian enterprises; on the other hand, the arrival of laborers and the redistribution of parts of the population of Carangas in the local mining camps. Among the results of these developements I want to focus the fact that half of the population that had emigrated from Carangas was living in mining camps, principally in Potosí. The sources present some difficulties to quantify these migrations, in particular to substantiate some categories that were previously used in this context - the forasteros. They include, however, the places of origin, information that facilitate migration analysis.